Legal complexities of the sex trafficking of minors - McCormick, Christie (2020)
Among human rights abuses in modern society, the trafficking of women and children for labor, prostitution, and other forms of sexual exploitation is one of the greatest. While a large amount of time and financial support has gone into efforts to suppress trafficking and shelter its victims, there has not been enough done to tackle this problem. Before reaching the age of 18, it is predicted that 80% of adolescents in the United States will have traded money for sex. Many adolescent girls who have been trafficked in the commercial sex industries are subject to serious criminal penalties for prostitution-related offenses regardless of being forced or coerced to commit these criminal acts against their will by either traffickers or pimps. At the present, more juveniles are finding themselves being adjudicated for sexual solicitation than are being found victims, and this outcome may be circumstantially based on a particular jurisdiction’s law. The purpose of this study will be to examine the judicial response to adolescent female human trafficking victims who are charged with the crime of prostitution. Specifically, how does the justice system respond to these under-aged prostitutes who are victims of human trafficking? Prior research has not looked at case law as a narrative source to unearth juridical decision making and how justice is dispensed for trafficked girls charged with prostitution. As such, this study applies a qualitative case law methodology that utilizes two layers of textual analysis to identify leading jurisprudential intent and discover the underlying themes of judicial temperament and convictions found within six court decisions, which make up the sample. Four prevailing themes emerged from the analyses, which best convey the jurisprudential intent of how and why the court ruled in these specific decisions. The four prevailing themes are: relief, best interest, rehabilitation, and individual accountability. Implications for policy and practice, as well as directions for future research, ensue from the discussion of these qualitative findings